Study on the ground impact vibration intensity model of high energy warhead explosion - Wang, Liangquan; Kong, Deren; Shang, Fei (Frontiers in Physics, 2023)
In the warhead explosion process, the ground impact vibration intensity will directly affect the target buildings and instruments safety, and it is also of great significance to accurately evaluate the ammunition explosion damage power. In this study, the finite element numerical simulation method was used to analyze the explosion shock wave pressure and ground shock vibration velocity of TNT explosive with a mass of 100 kg 1000 kg, and the ground transmission medium of sandy soil, C35 and C140 concrete, and the shock wave pressure and ground shock vibration velocity propagation and distribution law was clarified. Based on the explosion similarity law and dimensional analysis method, a ground impact vibration velocity theoretical calculation model with clear physical significance is established by introducing the property ground propagation medium parameters, taking into account the factors affecting the ground impact vibration velocity. The model calculation accuracy is verified by the measured data. The verification results show that the model calculation accuracy is higher than 91.8%, which improves the calculation accuracy of the explosion site ground impact vibration velocity. This research provides more accurate and scientific theory and data support for the ammunition explosion damage power evaluation, and provides a reference for the shock and vibration resistance performance design of instruments, equipment and buildings. It has strong engineering application value.